2019
DOI: 10.1002/cam4.2232
|View full text |Cite
|
Sign up to set email alerts
|

CLEC3A, MMP7, and LCN2 as novel markers for predicting recurrence in resected G1 and G2 pancreatic neuroendocrine tumors

Abstract: Although the postoperative recurrence rate for pancreatic neuroendocrine tumors (PNETs) is reported to be 13.5%‐30%, the paucity of valuable biomarkers to predict recurrence poses a problem for the early detection of relapse. Hence, this study aimed to identify new biomarkers to predict the recurrence of PNETs. We performed RNA sequencing (RNA‐Seq) on RNA isolated from frozen primary tumors sampled from all localized G1/G2 PNETs resected curatively from 1998 to 2015 in our institution. We calculated differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In this study, we identified LCN2 as a potential regulator of vitamin D. LCN2, also known as neutrophil gelatinase-associated lipocalin (NGAL), is a tumour- This finding was validated with our laboratory findings, clarifying that LCN2 is a tumour chemosensitive gene and has potential as a predictor of tumour recurrence 31 . Furthermore, we experimentally proved that the regulation of LCN2 and VDR genes is independent of each other.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, we identified LCN2 as a potential regulator of vitamin D. LCN2, also known as neutrophil gelatinase-associated lipocalin (NGAL), is a tumour- This finding was validated with our laboratory findings, clarifying that LCN2 is a tumour chemosensitive gene and has potential as a predictor of tumour recurrence 31 . Furthermore, we experimentally proved that the regulation of LCN2 and VDR genes is independent of each other.…”
Section: Discussionsupporting
confidence: 70%
“…Quantitative methylation-specific PCR (qMSP) was performed as described previously 31 . Briefly, genomic DNA was isolated with a Genomic DNA Purification Kit (Thermo Fisher Scientific, Cat.…”
Section: Quantitative Methylation-specific Pcrmentioning
confidence: 99%
“…pNET patients with G3, distant metastasis, larger tumor diameter, AJCC 8th III-IV stage, the white race, or age > 60 years old were associated with a worse OS/CSS. A higher pathological grade and lower differentiation of tumor cells indicate the tumor may be more malignant [ 13 , 14 ], some pNET patients with distant metastasis are difficult to treat since the removal of the primary and metastatic tumors may be impossible, and most of them can only achieve R1 or R2 resection [ 8 ]. Their prognosis is poorer than patients with an R0 resection.…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 has been implicated in the progression of several types of human tumors. LCN2 expression is higher in solid tumors than in corresponding normal tissues [24,41], and it is mainly described as tumor promoter in many cancers, including pancreas, glioblastoma, thyroid, kidney, esophagus, and breast cancer [20,28,[42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%